Dramatic Elements in Shakespeare’s Plays: Othello as a Sample - Yasir Dhain, Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
This study is distinctively restricted to the study of important features of Shakespeare’s tragic plays. It deals with three dramatic elements in Shakespeare’s plays, such as characters, tragic flaw, and soliloquy. He uses characters that represent high class, such as kings, barons, princesses, and fools. The protagonist sometimes has a weak point, which leads to his end. This defect is called a tragic flaw. A soliloquy is the way in which the character talks to himself either aloud or silently. This study deals with Shakespeare’s Othello as a sample in analyzing these important aspects. This study hypothesizes that these literary terms or dramatic elements are so important in Shakespeare’s plays. It is divided into eight sections, each analyzing a topic. Finally, the study has reached some conclusions that verify the hypothesis of the study.